Sobre a conjectura de Yau para estimativa do primeiro autovalor de hipersuperfícies mínimas compactas mergulhadas na esfera - Leite, Douglas Eliakim Lima da Silva (2024)
A problem proposed by Yau (1982) is whether the fi rst eigenfunction λ1 of a minimal hypersurface embedded in the sphere Sn+1 is equal to n. In this work we will demonstrate a result from Takahashi (1966) which states that λ ≤ n. Furthermore, when we develop some curvature tensors applied to the sphere,we will carry out an analytical study mainly regarding the conjecture. Our main objective, then, is to present results in two areas specific to the problem: for the first, it would be to propose conditions to guarantee equality λ1 = n; the second would be to present conditions that guarantee an explicit lower quota for λ better than n/2.